MANAGEMENT OF INNOVATIVE ACTIVITIES OF INDUSTRIAL ENTERPRISES IN THE CONDITIONS OF DIGITAL TRANSFORMATION - Charkina, Tatyana (Current Problems of Sustainable Development, 2026)
The article considers the current problems of managing the innovation activities of industrial enterprises in the context of digital transformation. The impact of digital technologies on the processes of innovation activity, in particular on the development, implementation and commercialization of innovative solutions, is analyzed. Special attention is paid to methods and approaches to innovation management, which allows increasing the efficiency of production processes, optimizing the use of resources and ensuring the competitiveness of enterprises in the modern market. The key challenges facing managers of industrial enterprises in the context of rapid technological changes are considered, as well as new digital management tools, in particular digital cooperation platforms, big data processing systems, artificial intelligence and the Internet of Things. The article contains recommendations on adapting management strategies and organizational models for the effective implementation of innovations in the digital era. The practical significance of the study lies in the formation of a comprehensive approach to innovation management, which contributes to the sustainable development of industrial enterprises and their integration into global digital ecosystems. The materials of the article may be useful for scientists, business leaders, and specialists in the field of innovation management and digital transformation. Innovation management in the context of digital transformation is becoming a key factor in the competitiveness of industrial enterprises. The implementation of digital technologies, such as Industry 4.0, the Internet of Things, artificial intelligence, big data, and others, requires a comprehensive management approach to effectively use the potential of innovation and minimize risks. Without systematic innovation management, enterprises risk losing their positions in the global market. Effective innovation management involves the formation of a clear strategy that correlates with the overall development strategy of the enterprise and takes into account the specifics of its industry. Such a strategy should cover the entire innovation cycle: from the generation of ideas and research to the introduction of new products, services, or processes and their subsequent scaling. A key element of the successful implementation of digital innovations is the development of an appropriate organizational culture and personnel competencies, which includes the formation of openness to change, readiness for experiments and learning, as well as the development of specific digital skills.